Body mass index and insulin resistance in healthy adults: Associations with plasma osteocalcin, phylloquinone levels, and dietary vitamin K intake - Ertaş Öztürk, Yasemin; Gezmen Karadağ, Makbule; Aktürk, Müjde; Şanlıer, Nevin (Progress in Nutrition, 2020)
The skeletal system is considered an endocrine organ today. Associations between bone Gla proteins, body mass index and insulin resistance are intriguing novel field due to being possible explanations for the interactions between bone and endocrine system. The aim of the present study was to investigate the associations between insulin resistance and body mass index (BMI) with plasma osteocalcin, phylloquinone levels and dietary vitamin K intakes in healthy non-obese adults. This cross-sectional study was conducted with 77 healthy non-obese adults. Anthropometric measurements and 24-hour food consumption record were taken from each individual. Blood glucose, insulin, osteocalcin (OC), undercarboxylated osteocalcin (ucOC), vitamin K levels were analyzed. The homeostasis model assessment for insulin resistance (HOMA-IR) value was calculated. Multiple linear regression models were performed using the backward method in order to determine the significant predictors of BMI and HOMA-IR. Mean age and BMI of the participants were 31.7±5.6 years and 24.6±3.04 kg/m2 respectively. After multiple regression analysis, BMI, dietary vitamin K intake and phylloquinone were significant predictors of HOMA-IR. Furthermore, ucOC and triglyceride were significant predictors of BMI. No significant association between OC levels and HOMA-IR values were shown. In healthy non-obese adults, ucOC may be related to decreasing BMI. Our data do not support that increased OC has a beneficial role against insulin resistance. Dietary vitamin K intake may have a protective effect on insulin resistance. Further studies should examine the clinical importance of these findings.